Analisis Implementasi Prinsip Good Governance dalam Meningkatkan Efektivitas SDM pada OPD Dinas Perikanan BBI Majaran Kabupaten Sorong - Paijan, Paijan; Pahmi, Pahmi; Irwan, Andi; Likewati, Waode (Jurnal EMT KITA, 2026)
The implementation of good governance principles plays an important role in enhancing the effectiveness of human resources (HR) in public sector organizations. This study aims to analyze the application of transparency, accountability, participation, responsiveness, effectiveness, and efficiency in improving HR effectiveness at the Fisheries Office, Fish Seed Center (BBI) Majaran, Sorong Regency. A descriptive qualitative approach was employed, using interviews, observations, and documentation. Informants included the head of the center, financial managers, administrative staff, and technical officers. Data were analyzed through data reduction, presentation, and conclusion drawing, with source and technique triangulation to ensure validity. The findings indicate that transparency, accountability, and participation have been implemented fairly well, particularly in information disclosure and task distribution. However, responsiveness, effectiveness, and efficiency remain suboptimal due to limitations in HR capacity, infrastructure, technological support, and dependence on parent agency policies. Strengthening HR management, capacity building, technology utilization, and institutional coordination is needed to achieve sustainable HR effectiveness.